How large is the wage penalty in the labour broker sector? Evidence for South Africa using administrative data - Aalia Cassim; Daniela Casale (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Public debate on the temporary employment services, or labour broker, sector in South Africa has focused on temporary workers' wages and benefits. Empirical research is limited: temporary employment services cannot be accurately identified in recent labour force surveys. In 2015, South Africa Revenue Services and the National Treasury made company and employee income tax data available which explicitly captures labour brokers and employee wages. We use this to examine whether there is a wage penalty for labour broker employees and, if so, its magnitude. We control for individual and time fixed effects. Such empirical evidence is important in debates on the sector's role in the South African labour market.
Keywords: J31; J41; 330; temporary employment services; wage differentials; administrative data; South Africa